Mutation-Based Learning to Improve Student Autonomy and Scientific Inquiry Skills in a Large Genetics Laboratory Course - Wu, Jinlu (American Society for Cell Biology, 2013)
Laboratory education can play a vital role in developing a learner's autonomy and scientific inquiry skills. In an innovative, mutation-based learning (MBL) approach, students were instructed to redesign a teacher-designed standard experimental protocol by a “mutation” method in a molecular genetics laboratory course. Students could choose to delete, add, reverse, or replace certain steps of the standard protocol to explore questions of interest to them in a given experimental scenario. They wrote experimental proposals to address their rationales and hypotheses for the “mutations”; conducted experiments in parallel, according to both standard and mutated protocols; and then compared and analyzed results to write individual lab reports. Various autonomy-supportive measures were provided in the entire experimental process. Analyses of student work and feedback suggest that students using the MBL approach 1) spend more time discussing experiments, 2) use more scientific inquiry skills, and 3) find the increased autonomy afforded by MBL more enjoyable than do students following regimented instructions in a conventional “cookbook”-style laboratory. Furthermore, the MBL approach does not incur an obvious increase in labor and financial costs, which makes it feasible for easy adaptation and implementation in a large class.